Antioxidant Activity of Biofield Treated Proprietary Test Formulation Supplemented with Vitamins and Minerals in Vitamin D3 Deficiency Diet (VDD) Induced Sprague Dawley Rats - Mahendra Kumar Trivedi; Alice Branton; Dahryn Trivedi; Snehasis Jana (Journal of Antioxidant Activity, 2021)
A proprietary formulation was designed that consisted minerals (zinc, magnesium, iron, calcium, selenium, and copper), vitamins (pyridoxine HCl, cyanocobalamin, ascorbic acid, and cholecalciferol), Panax ginseng extract, and cannabidiol isolate. The study was aimed to assess the potential of the novel test formulation (blessed) and per se to the animals with the Trivedi Effect® in male Sprague Dawley (SD) rats, fed with vitamin D3 deficiency diet (VDD). The test formulation consisted above mentioned ingredients was divided into two parts. One part was left aside as the untreated test formulation without any Biofield Treatment, while the other part was defined as the Biofield Energy Treated sample, which received the Biofield Treatment by renowned Biofield Energy Healer, Mr. Mahendra Kumar Trivedi. The level of lipid peroxidation end product malondialdehyde (MDA) in liver tissues was significantly reduced by 34.59%, 34.91%, and 65.81% (p≤0.001) in test formulation treated with Biofield Energy (G5), Biofield Treated test formulation from day -15 (G7), Biofield Treatment per se with Biofield Treated test formulation from day -15 (G8) groups, respectively as compared to the disease control group (G2). Moreover, level of catalase enzyme in liver tissues was also increased by 8.64% in the G7 group as compared to the G2 group. Besides, in brain homogenate the level of glutathione peroxidase (GPx) was significantly increased by 433.94%, 266.97%, 133.94%, 467.89%, and 489.86% in the G5, Biofield Energy Treatment per se to animals from day -15 (G6), G7, G8, and Biofield Treatment per se animals plus untreated test formulation (G9) groups, respectively than G2. Antioxidant enzyme like superoxide dismutase (SOD) was significantly (p≤0.001) increased by 14.16% in the G9 group as compared to the G2 group. Allover, results signified that the Biofield Treated test formulation significantly increased antioxidative parameters, could be able to give support against oxidative stress induced by free radical and to maintain a good human health.
Keywords: Antioxidant Activity